PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PASIEN SERTA DAMPAKNYA TERHADAP LOYALITAS PASIEN RUMAH SAKIT ISLAM KARAWANG - Yolanda Yolanda; Edi Sumedi (Jurnal Manajemen FE-UB, 2018)
The condition of competition in health care industry is very tight. This is due to the increasing number of existing clinics and hospitals, as well as the increasing number of people using hospital facilities to obtain health services. The hospital, which was originally more of a public service unit of a social humanitarian nature, in fact hospital services and health care organizations have undergone transformation and evolved into an industry based on economic principles and management as commercial ventures. However, the most important thing in the health care industry (Hospital) is the quality of service provided by the hospital to the patient.This study aims to analyze deeper the Influence of Service Quality (X1) and Price (X2) on Patient Satisfaction (Y) and its impact on Loyalty (Z).Sempel taking technique using accidental sampling is based on chance which means Patients who went to the Islamic Hospital in Karawang, with the number of samples obtained as much as 98 respondents. Data analysis technique used in this research is by Path Analysis method and using analysis tool that is SPSS 22.The test results indicate that the variable of Service Quality has positive and significant influence directly to Patient Satisfaction. Price has positive and significant effect directly to Patient Satisfaction. service quality has positive and significant effect directly to patient loyalty. price has an effect on positive and significant directly to patient loyalty. patient satisfaction has a positive and significant effect on patient loyalty. there is a positive influence and indirectly significant service quality to patient loyalty. there is a positive and indirectly significant influence between price and loyalty of the patient. Keywords : Quality of Service, Price, Patient Satisfaction, and Patient Loyalty